Human biomonitoring in Australian children: Brominated flame retardants decrease from 2006 to 2015. (January 2019) - Drage, Daniel S.; Harden, Fiona A.; Jeffery, Tomas; Mueller, Jochen F.; Hobson, Peter; Toms, Leisa-Maree L.
Abstract: Polybrominated diphenyl ethers (PBDEs) and hexabromocyclododecane (HBCDD) were used intensively as flame retardants, worldwide. They have been detected in human serum samples and PBDEs have been found to be elevated in young children. Commercial Penta- and Octa-PBDE mixtures were banned in Australia in 2005, while HBCDD was banned worldwide in 2013. We investigated PBDE and HBCDD concentrations in serum collected from young children. We also investigated temporal trends in PBDE concentration 10 years after their Australian ban. Surplus human blood serum samples were collected through a pathology clinic ( n  = 800), in 2014/15, stratified by age (0–6, 6–12, 12–18, 18–24, 24–30, 30–36, 36–42, 42–48, 48–54 and 54–60 months) and sex and pooled for analysis of PBDEs (BDEs −28, −47, −99, −100, −153, −154, −183) and HBCDD. In 2014/15, the geometric mean concentration of the sum of all PBDEs measured (ΣPBDEs) was 4.5 ng/g lipid (median: 4.6 ng/g lipid, range: 0.88–26 ng/g lipid). A positive association between BDE-47 concentration and age was observed ( R  = 0.41, p  = 0.008), however there were no trends between other PBDE congeners or HBCDD and age. There were no significant differences between genders for PBDEs ( t -test, p  = 0.802) or HBCDD (t-test, p  = 0.740).The highest concentrations observed were in pools from the females 30–36 month (26 ng/g lipid) and Males 6–12 month (21 ng/g lipid) categories. BDEs −47 and −99 were the predominant congeners with a combined average contribution of 75% of ΣPBDEs. PBDEs showed a significant reduction in children aged 0–4 years over an eight year period. In 2014/15, the mean (range) concentration of BDE-47 is 2.8 (0.23 to 11) ng/g lipid compared to pools in 2006/07 at 19 (3–55) ng/g lipid ( p  < 0.0001) and for BDE-153 is 0.73 (<0.1 = −2.9) ng/g lipid compared to pools in 2006/07 at 4.7 (2−10) ng/g lipid ( p  < 0.0001). HBCDD concentrations were lower than PBDEs with a mean concentration of 0.45 ng/g lipid. There were no temporal trends observed for HBCDD when compared to samples collected in 2012. The dominant stereoisomer was α-HBCDD (mean = 0.38 ng/g lipid) with an average contribution of 65% towards ΣHBCDD. Levels of PBDEs in young Australian children have significantly decreased since the bans of commercial Penta- and Octa-BDE in 2005. There has been no observed decrease in HBCDD levels in Australian children since its ban in 2012. Highlights: PBDEs and HBCDD measured in serum from Australian children. PBDEs have decreased in concentration by >85% since commercial bans. HBCDD levels low in comparison to PBDEs. No decrease observed in HBCDD levels yet.